Performance Degradation Law and Model Construction of Hydraulic Concrete Under Freeze-Thaw Cycles: A Comprehensive Review - Xiangyi Zhu; Xiaohe Zhou; Yuxuan Xia; Xudong Chen (Buildings)
Hydraulic concrete structures in cold regions often suffer from the combined action of freeze-thaw (FT) cycles and external loads, indicating that these structures often depend on the combined effects of two or more factors. In recent years, researchers around the world have made considerable efforts and explorations to solve this challenge, achieving fruitful research results. This article provides a comprehensive literature review on performance degradation law and model construction of hydraulic concrete under FT cycles. Firstly, the theory and characterization method of FT damage for concrete are introduced. Given the inherent deficiencies of traditional detection methodologies and the constraints imposed by extant computed tomography (CT) technology, there is an urgent need to develop a high-precision segmentation technique for concrete. By capitalizing on the resultant microstructure, a more accurate predictive model can be established. Thereafter, an in-depth discussion is conducted on the damage mechanism of hydraulic structures when subjected to freeze-thaw (FT) cycles in conjunction with external loading scenarios, namely fracture, direct tension, triaxial stress, and hydraulic wear. As the combined effects of different factors cause more serious damage to hydraulic structures than a single factor, the evolution law is more complex. Although researchers have attempted to reveal the deterioration mechanism of multi-factor interaction by means of numerical methods, there are still many fundamental issues that require further exploration and more in-depth research due to the limitations of constitutive models. Finally, the existing research results are summarized, and novel insights are proposed for future research directions. This study promptly identifies the gaps that urgently need to be filled, especially the insufficient understanding of the complex stress state of hydraulic concrete structures and the inadequate research on the performance deterioration law under multi-factor combined action. This investigation aims to determine the future research focus in relation to hydraulic concrete in cold regions that could advance the revelation of the deterioration mechanism caused by multi-factor interaction. By providing a detailed overview of the current hydraulic concrete structures in terms of the combined action of FT cycles and external loads, highlighting the research limitations, and suggesting future research directions, this review seeks to contribute to the safe operation of hydraulic concrete structures in cold regions.